Measure and comparison of speech pause duration in subjects with disfluency speech - Teixeira, João Paulo (2014)
This work has the goal of comparing the pause duration in the disfluency speech and normal speech. Disfluency and normal spontaneous speech was recorded in a context were the subjects had to describe a scene from each other. The pause determination algorithm was developed. The automatic pause determinations allowed the measure of percentage of silence along the record of several minutes of speech. As expected these parameters is rather different in subjects with and without disfluency speech, but it do not seems that it is proportional to the severity of the disfluency.